Impact of pharmaceutical R&D activity on financial flexibility and bargaining power - Gergő Tömöri; Zoltán Bács; János Felföldi; Ildikó Orbán (Economies, 2022)
The specificities of pharmaceutical companies' activities also have an impact on their ability to improve profitability compared to other sectors. Examples of such specificities include patent rights on the medicines produced, which for a longer period of time prevent the entry of competing players, allowing sunk costs to be offset to some extent by advantages from using higher margins. The primary purpose of this study is to examine whether the bargaining power of R&D-engaged companies significantly affects the financial margin of their operations to a different extent than other pharmaceutical companies. This study examined panel data focused on companies with the highest turnover, while we filtered out differences in the effect due to different macroeconomic and development environments. Our findings are that while the gross profit was significantly influenced by the type of activity within the industry, this statement for the cash cycle is no longer justified. Our conclusion was that the difference between the engaged and non-engaged in R&D companies expressed mostly in the profitability ratios, besides that, countries which had different development policies and accounting systems also took impact on financial margins, although the relative GDP advantages disappeared when looking at intra-industry, cross-country movements.
Keywords: 330; bargaining power; cash cycle; development policies; industry leaders; panel regression; pharmaceutical industry; profitability; R&D